The psychological parameters of athletic injuries in female collegiate athletes - Stewart-Reiner, C. C. (International Journal of Human Movement and Sports Sciences, 2020)
Introduction/Purpose: The purpose of this study was to determine if there is a difference in the psychological parameters of life stress and anxiety as risk factors to injury. Methods: Participants in this study are female athletes [n=51, (36 injured, 15 non-injured)] from four various sports teams (basketball, golf, soccer, and softball) at an NCAA Division I college. The participants completed four different questionnaires: an injury report, the Life Events Coping Scale for Collegiate Athletes (LESCA), the Sport Anxiety Scale (SAS), and the Sport Competition Anxiety Test (SCAT). Results: Results indicated that injured athletes experienced more life stress than non-injured athletes and this difference was statistically significant. Results also showed that in personality competitive anxiety and sport competitive anxiety, non-injured athletes have lower anxiety than injured athletes. Conclusion: This study sought to examine the differences in injured and non-injured athletes between psychological parameters that may lead to injury. The difference in life events between injured and non-injured athletes was statistically significant while the difference in personality competitive anxiety and sport competitive anxiety was not statistically significant.